A randomized phase II study of LY2510924 and carboplatin/etoposide versus carboplatin/etoposide in extensive‐disease small cell lung cancer. (March 2017) - Salgia, Ravi; Stille, John R.; Weaver, R. Waide; McCleod, Michael; Hamid, Oday; Polzer, John; Roberson, Stephanie; Flynt, Amy; Spigel, David R.
Highlights: Addition of LY2510924 to SOC did not improve PFS or OS in extensive-disease SCLC. The combination was relatively safe and tolerable. Abstract: Objectives: This multicenter, open-label, randomized phase II study evaluated the efficacy and safety of LY2510924 (LY) added to first‐line standard of care (SOC) chemotherapy for extensive-disease small cell lung cancer (ED-SCLC) and explored the predictive value of C‐X‐C motif receptor 4 (CXCR4) tumor response. Materials and methods: Patients with treatment-naïve ED-SCLC were randomized (1:1) to receive up to six 21-day cycles of carboplatin/etoposide alone (SOC) or in combination with 20 mg LY2510924 administered subcutaneously on days 1–7 of each cycle (LY + SOC). The primary efficacy endpoint was progression‐free survival (PFS). Secondary endpoints were overall survival (OS), overall response rate (ORR), and safety. Response relative to CXCR4 expression on baseline tumor was an exploratory endpoint. Results: Of 94 patients randomized, 90 received treatment (LY + SOC, n = 47; SOC, n = 43). Median PFS (95% confidence interval [CI]) was 5.88 (4.83, 6.24) months for LY + SOC versus 5.85 (4.63, 5.51) months for SOC (hazard ratio [95% CI], 1.01 [0.62, 1.63]; p  = 0.9806). Median OS (95% CI) was 9.72 (6.64, 11.70) months for LY + SOC versus 11.14 (8.25, 13.44) months for SOC. ORR was 74.5% for LY + SOC versus 81% for SOC. Safety results between arms were similar, although the following adverse events were more frequent on the LY + SOC arm: anemia (61.7% vs 46.5%), neutropenia (61.7% vs 53.5%), leukopenia (27.7% vs 9.3%), vomiting (27.7% vs 16.3%), and pneumonia (10.6% vs 2.3%). In patients whose baseline CXCR4 expression was above the optimal cutoff (H‐score 210), the hazard ratio (95% CI) was 1.27 (0.51, 3.15). Conclusion: LY2510924 did not improve efficacy but had an acceptable toxicity profile when added to SOC for ED‐SCLC.